2017
DOI: 10.1016/j.jtcvs.2016.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling root repair with an external aortic ring annuloplasty

Abstract: The standardization of remodeling root repair with calibrated expansible aortic ring annuloplasty and cusp effective height assessment improves valve repair outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 30 publications
3
106
3
Order By: Relevance
“…Since 2003, we have operated on 482 patients using this standardized approach with 92% freedom for reoperation at 8 years similar for bicuspid and tricuspid valves according to each phenotype of the proximal aorta. Furthermore, since 2007 we have used systematic eH assessment and expansible calibrated annuloplasty ring (Extra-Aortic; CORONEO, Inc., Montreal, QC, Canada) with the remodeling process, which has improved freedom from AI grade ≥3 (100%), re-operation (99.1%) and major adverse valve-related events (96.3%) at 7 years follow-up with similar results for bicuspid and tricuspid valve repair (53). Systolo-diastolic expansibility of the annulus was preserved following the annuloplasty (5.1%±9.5%) (54).…”
Section: Aortic Annuloplasty: a Standardised Approach To Av Repairmentioning
confidence: 93%
“…Since 2003, we have operated on 482 patients using this standardized approach with 92% freedom for reoperation at 8 years similar for bicuspid and tricuspid valves according to each phenotype of the proximal aorta. Furthermore, since 2007 we have used systematic eH assessment and expansible calibrated annuloplasty ring (Extra-Aortic; CORONEO, Inc., Montreal, QC, Canada) with the remodeling process, which has improved freedom from AI grade ≥3 (100%), re-operation (99.1%) and major adverse valve-related events (96.3%) at 7 years follow-up with similar results for bicuspid and tricuspid valve repair (53). Systolo-diastolic expansibility of the annulus was preserved following the annuloplasty (5.1%±9.5%) (54).…”
Section: Aortic Annuloplasty: a Standardised Approach To Av Repairmentioning
confidence: 93%
“…We feel that an external device is most likely superior because of better stress distribution and avoidance of interference with the aortic valve cusps. Of the external devices, different rings have been employed (14,15). In the presence of a high aortoventricular junction the implantation of an external ring may be difficult and might lead to anatomic distortion or would require deep circumferential dissection (15).…”
Section: Commentmentioning
confidence: 99%
“…Similarly de Kerchove and colleagues [12] found improved results with VSRR than with SCA, reporting freedom from reoperation and AI greater than 2þ better for the VSRR than for SCA (100% versus 90% and 100% versus 77%, respectively). Recently, Lansac and colleagues [23] reported good valve repair durability and annular stabilization with an expansible aortic ring annuloplasty. In their study they found a 7-year freedom from valve-related reoperation of 99.1%, freedom from valve-related events of 96.3%, freedom from AI grade 3 or Cumulative hazards estimates.…”
Section: Commentmentioning
confidence: 99%